The Right to Freedom of Religion or Belief of Minority Communities - Badurdeen, Fathima Azmiya (The review of faith & international affairs, 2026)
Policy efforts on the right to freedom of religion or belief (FoRB) often focus on the protection of vulnerable religious minorities. Yet focusing solely or primarily on religious minorities overlooks the needs of other minorities whose rights are also protected under Article 18. Such vulnerable groups include atheists, indigenous spiritualities, and the LGBTQIA + community. Drawing on data collected in Kenya and Indonesia as part of the Joint Initiative on Strategic Religious Action (JISRA) project, this article highlights persistent challenges for minorities that FoRB projects do not always successfully address. It offers policy, research, and civil society recommendations aimed at enhancing protections for oft-neglected minorities.